Evaluation of BER for the EHF Communication System Serving Sharp-Coned Reentry Vehicles - Yang, Xiaocui; Yuan, Kai; Wang, Yuhao; Liu, Yiwen (Frontiers in Earth Science, 2022)
“Communication blackout” could lead to severe risks to reentry vehicles. Previous studies have shown that EHF (Extremely High Frequency) communication is a potential solution to the “communications blackout” and was mostly used for blunt coned vehicles. EHF communication with sharp coned vehicles is rarely concerned before. In the present study, the propagation characteristics of the modulated EHF signals in time-varying plasma sheath covering sharp coned vehicles were studied numerically. The plasma sheath was obtained by solving a hypersonic fluid dynamics model. The signals propagation model is developed based on geometric optical theories. The carrier frequencies concerned in the present study are the “atmospheric window” frequencies, which are 94 GHz, 140 GHz and 225 GHz, respectively. Based on the signals propagation characteristics, the EHF communication system was modeled. The modulation modes concerned in the present study are the 2ASK, 2PSK and 2FSK, respectively. The results show that: (1) the transmission coefficient of EHF signals in the side channel of plasma sheath of sharp coned reentry vehicle increases with carrier frequency, (2) the gap between different channels at specific carrier frequency decreases with time, (3) the phase shift tends to be stable as the carrier frequency increases, (4) the BER varies with time, and is affected by the location of the onboard antenna, carrier frequency and modulation mode. The study shown that, in order to achieve good BER performance for the EHF communication system, the signals are suggested to be phase modulated at 140 GHz, and the onboard antenna is suggested to be installed on the wall and close to the bottom of sharp coned vehicle.